Short Communication: New records of aphid species Subfamily Aphidinae (Hemiptera: Aphididae) in West Java, Indonesia - YANI MAHARANI; PURNAMA HIDAYAT; AUNU RAUF; NINA MARYANA (Society for Indonesian Biodiversity, 2018)
Maharani Y, Hidayat P, Rauf A, Maryana N. 2018. Short Communication: New records of aphid species Subfamily Aphidinae (Hemiptera: Aphididae) in West Java, Indonesia. Biodiversitas 19: 510-515. Aphids (Hemiptera: Aphididae) are an economically important group of insects. Their feeding not only damages crops directly but also transmits viruses that cause plant disease. The total number of aphid species recorded in West Java, Indonesia between 1917 and 2013 was 184 species. The aim of the study reported here was to identify and record any aphid species and their host plants in West Java Province, Indonesia that had not previously been recorded. The study was conducted in thirteen districts in West Java. Fourteen species of aphid were newly recorded as found in West Java; five species from the tribe Aphidini, and nine species from the tribe Macrosiphini.